Vivax malaria: a possible stumbling block for malaria elimination in India - Kumar, Ashwani; Singh, Puspendra Pal; Tyagi, Suchi; Hari Kishan Raju, K.; Sahu, Sudhanshu S.; Rahi, Manju (Frontiers in Public Health, 2024)
Plasmodium vivax is geographically the most widely dispersed human malaria parasite species. It has shown resilience and a great deal of adaptability. Genomic studies suggest that P. vivax originated from Asia or Africa and moved to the rest of the world. Although P. vivax is evolutionarily an older species than P. falciparum, its biology, transmission, pathology, and control still require better elucidation. P. vivax poses problems for malaria elimination because of the ability of a single primary infection to produce multiple relapses over months and years. P.vivax malaria elimination program needs early diagnosis, and prompt and complete radical treatment, which is challenging, to simultaneously exterminate the circulating parasites and dormant hypnozoites lodged in the hepatocytes of the host liver. As prompt surveillance and effective treatments are rolled out, preventing primaquine toxicity in the patients having glucose-6-phosphate dehydrogenase (G6PD) deficiency should be a priority for the vivax elimination program. This review sheds light onhighlights the burden of P. vivax, changing, epidemiological patterns, the hurdlestrends, challenges in elimination efforts, and the essentialnew tools needed not justnecessary to eliminate vivax malaria in India but globally. These tools encompass innovative treatmentsand elsewhere; such as new short-duration treatment modalities for eliminating dormant parasites, copinghypnozoite elimination as anti-relapse drugs, new effective drugs to deal with evolving drug emerging chloroquine resistance, and the development of potentialtransmission-blocking vaccines against the parasite. .